Aerosol vertical profile variations with seasons, air mass movements and local PM2.5 levels in three large China cities. (1st March 2020) - Wang, Lingyu; Lyu, Baolei; Bai, Yuqi
Abstract: High atmospheric aerosol densities in China have significant influence on air quality and human health. It is critical to understand their variations with seasons, air qualities and regional meteorological conditions, not only in the horizontal dimension but also in the vertical dimension. In this study, we discussed aerosol vertical profiles from spaceborne lidar in different seasons, regional air mass movement patterns and ground-level PM2.5 concentrations in three large China cities of Beijing, Shanghai and Guangzhou. The extinction coefficient profiles exhibited apparent seasonal variations due to varied emission and meteorological conditions. Characterized by backward trajectories, the air mass movements, especially the moving speeds and their source regions, have strong impacts on both extinction coefficient values and its relative profile structures. The aerosol extinction coefficient values had positive correlation with ground-level PM2.5 concentrations within the altitude below 700 m, while the relationship in higher altitudes was inapparent. As the altitude increased, the mean extinction coefficient values of high PM2.5 clusters sharply decreased, while the extinction coefficient values of low PM2.5 clusters declined in a linear pattern with a gentle slope. This study provided insightful analysis to understand the vertical distributions of aerosol extinction coefficients under different scenarios, which is helpful for better understanding air pollution episodes. Highlights: The aerosol extinction profiles exhibited apparent seasonal variations. The air masses movement velocity and their sources influenced aerosol profiles. Extinction coefficient decreased sharply as height increased in high PM2.5 levels. Aerosol profiles decreased linearly with a gentle slope in low PM2.5 levels.